The MORPHOLOGY AND MOLECULAR CHARACTERIZATION OF TYLENCHULUS SEMIPENETRANS FROM CITRUS ORCHARDS IN NORTHERN IRAN: MORPHOLOGY AND MOLECULAR CHARACTERIZATION OF TYLENCHULUS SEMIPENETRANS - Jamali, Salar (Journal of Agricultural Sciences (Belgrade), 2023)
Tylenchulus semipenetrans Cobb, 1913 is among some of the most economically important plant parasitic nematodes in the world. The nematode was identified as the causal agent of slow decline and can cause 10-30% losses reported on citrus trees. Citrus nematode was collected and identified from north of Iran. Morphological observations as well as molecular evidence confirmed this population as T. semipenetrans. A phylogenetic tree of T. semipenetrans populations were reconstructed based on 28S rRNA gene sequences using RAxML. On a basis of molecular analysis Tylenchulus was recovered as a monophyletic group. The phylogenetic position and measurements of T. semipenetrans were provided.
Keywords: 28S rRNA, citrus, Iran, molecular analysis, phylogeny, Tylenchulus semipenetrans